Dukungan Emosional Keluarga pada Rencana Pemilihan Penolong Persalinan Di Puskesmas Rumpin Kabupaten Bogor - Rubbyatul Aulia; Lola Noviani Fadilah; Rika Resmana; Desmaniarti Z (Midwifery Care Journal, 2024)
Bogor district contributes the largest MMR in West Java Province. Rumpin sub-district in Bogor district has quite low numbers for birth assisted by health worker. A study says that one of the causes is lack of family emotional support. Find out relations between family emotional support with birth attendant selection plan in Rumpin Public Health Bogor District. The research is used analytical research with a cross sectional design. The population of the study was pregnancy woman 3rd trimester and conducted at the Rumpin Public Health Center in 2023 as many as 83 respondens. Analysis using the Chi-Square test showed that the P-value was 0,007 or there was a relationship between family emotional support with birth attendant selection plan with an OR of 6,125. Pregnancy woman with low family support were 6,125 times more likely to plan to choose non-health workers as a birth attendant. There is a relations between emotional family support with birth attendant selection plan in Rumpin Public Health Center Bogor District